抗SRP抗体陽性の重症多発性筋炎に免疫グロブリン大量療法(IVIG)が奏効した一例 - 田崎, 知江美; 木下, 浩二; 嶋津, 秀紀; 井上, 明日圭; 廣岡, 靖章; 朝戸, 佳世; 岸本, 和也; 樋野, 尚一; 志賀, 俊彦; 松村, 到; 船内, 正憲; 矢野, 智洋; et al. (臨床リウマチ, 2014)
The idiopathic inflammatory myopathies are systemic autoimmune diseases characterized by chronic inflammation, leading to progressive weakness of the proximal muscles. Myositis-specific or associated autoantibodies are often found in the serum of polymyositis (PM) and dermatomyositis patients. Anti-SRP (signal recognition particle) antibody is thought to be associated with severe forms of the disease, particularly those with heart and lung involvement and resistant to adrenocorticosteroids. We present a66-year-old female polymyositis patient with serious muscle weakness and high CPK level (21550IU/L). Despite initial therapy with high-dose methylprednisolone (1g/day x3days,i.v.) followed by prednisolone (1mg/kg/day,p.o.) plus cyclosporine A (150mg/day), muscle weakness was not improved and CPK levels were not reduced to less than3000IU/L. After treatment with intravenous immunoglobulin (IVIG), muscle strength was gradually improved and CPK levels were reduced to less than700IU/L. To our knowledge, there were few reports that PM positive for serum anti-SRP antibody treated with IVIG. IVIG might be a therapeutic agent of choice for steroid-resistant cases of serum anti-SRP antibody-positive PM.